Clinical outcomes and risk factors associated with neonatal transports in Switzerland: a retrospective single-centre cohort study (Swiss Medical Weekly, 2025)
OBJECTIVE: To assess the association of patient and transport characteristics with mortality and morbidity of neonates who require interfacility transport in central Switzerland.METHODS: We conducted a retrospective single-centre cohort study including neonates transported by the neonatal transport service of the Bern University Children՚s Hospital between January 2019 and December 2022. We reviewed the transport protocols and electronic patient charts of the hospitalisation after transport, and investigated the association of patient characteristics, clinical management before transport and transport characteristics (transport mode, transport times, adverse events) with outcomes. The primary outcome was death or impairment; secondary outcomes were lengths of stay in the intensive care unit and hospital, inotrope-free days and respiratory support-free days following transport.RESULTS: Of 807 neonates who were included, 105 (13%) showed an unfavourable outcome (death: 25 patients, impairment at time of discharge: 80). We observed a significant association between patients’ diagnosis and primary outcome (p